Student-Data Ban Faces Test. - WILKINS, EMILY (CQ Magazine, 2016)
The article reports that the U.S. student privacy law which banned the Education Department from collecting student data, has set into test following concerns on its implication to the college students. Topics include the significant of data on helping students and families on decision making, the concern on the security risk of the proposed information system, and the significant of unit record system on answering policy-related concerns.